Analysis of surface water contamination by heavy metal from Demak Laut Industrial Park - Elvy Sukarsih, Gerem (Universiti Malaysia Sarawak (UNIMAS), 2014)
Surface water is the main source of available water which is getting polluted all over the world in many ways. Anthropogenic activities are the main causes of the pollution. The main sources of toxic heavy metals were possible wastewater and effluents from major industries, especially the chemical, polymer, metal, petrochemical gas and energy, and wooden industries that generated the organic and inorganic pollutions which ultimately contaminated the river water. Therefore, the main objective of this study is to monitor the heavy metal contamination in Sungai Santubong, which is closed to industrial park in Kuching, Sarawak named Demak Laut Industrial Park) This industrial park comprises of industrial of wood processing, furniture manufacturing, food processing and some machinery factory. After the construction of the barrage, this industrial park is not connected to Sungai Sarawak anymore and its discharge is directed to Sungai Santubong. River water was sampled at 10 cm and 1 m below the surface river water using Depth Sampler. Collected water samples were transferred into 200 millilitre plastic bottle and acidified to pH 2 using nitric acid. All water samples were kept in ice box at 4 ·C and transported to the laboratory for analysis. Portable Data logging Colorimeter DRl890 and Atomic Absorption Spectrophotometer (AAS) were used to analyse water sample for detection of Cd, Pb and As. Reagents and quality assurance high purity chemicals and reagents were purchased from Merck and Aldrich Chemical Company. Zn and N i have significant concentration at 10 cm and 1 m depth above surface river water. Whereas others heavy metals have no sigrrificant different at 10 cm and 1 m depth above surface river water. The concentration of Cd at 10 cm and I m depth from surface river water is 0.02 mg/L in level allowed based on Standard B Environmental Quality Regulation (Discharge and Industrials Effluent) 1979 where the requirement based on Standard B is 0.02 mg/L. Other heavy metals are below Standard B requirement. Only Fe and Ni have significant different concentration at 10 cm and 1 m depth above surface river water.